Volunteering and life or financial shocks: Does income and wealth matter? - Tony Beatton; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Volunteering is a dominant social force that signals a healthy state. However, although the literature on volunteering is extensive, knowledge on how life's discontinuities (life event shocks) affect volunteering is limited because most studies work with static (cross-sectional) data. To reduce this shortcoming, we use longitudinal data from Australia (HILDA) that tracks the same individuals over time to assess how individuals from different income and wealth groups respond to life and financial shocks with respect to volunteering. Although both income and wealth can act as buffers against life shocks by providing stability and reducing vulnerability—which decreases the need to actually change behaviour patterns— we observe more heterogeneity than expected and also stickiness at the lowest income levels. Response delays in post-shock volunteering also suggest that volunteering habits may be driven and influenced by strong commitment and motivation that are not shattered by life or financial shocks. In fact, the amount of time spent volunteering tends to increase after negative income shocks and decrease after positive income shocks.
Keywords: D64; J22; D31; Z13; N37; 330; volunteering; life event shocks; financial shocks; income; wealth; habits; panel; Australia